Advancements in the nanodelivery of azole-based fungicides to control oil palm pathogenic fungi - Asmawi, Azren Aida; Adam, Fatmawati; Mohd Azman, Nurul Aini; Abdul Rahman, Mohd Basyaruddin (Elsevier, 2024)
The cultivation of oil palms is of great importance in the global agricultural industry due to its role as a primary source of vegetable oil with a wide range of applications. However, the sustainability of this industry is threatened by the presence of pathogenic fungi, particularly Ganoderma spp., which cause detrimental oil palm disease known as basal stem rot (BSR). This unfavorable condition eventually leads to significant productivity losses in the harvest, with reported yield reductions of 50–80 % in severely affected plantations. Azole-based fungicides offer potential solutions to control BSR, but their efficacy is hampered by limited solubility, penetration, distribution, and bioavailability. Recent advances in nanotechnology have paved the way for the development of nanosized delivery systems. These systems enable effective fungicide delivery to target pathogens and enhance the bioavailability of azole fungicides while minimising environmental and human health risks. In field trials, the application of azole-based nanofungicides resulted in up to 75 % reduction in disease incidence compared to conventional fungicide treatments. These innovations offer opportunities for the development of sustainable agricultural practices. This review highlights the importance of oil palm cultivation concerning the ongoing challenges posed by pathogenic fungi and examines the potential of azole-based fungicides for disease control. It also reviews recent advances in nanotechnology for fungicide delivery, explores the mechanisms behind these nanodelivery systems, and emphasises the opportunities and challenges associated with azole-based nanofungicides. Hence, this review provides valuable insights for future nanofungicide development in effective oil palm disease control.